Oncogenic transformation by by equine herpesviruses. II. Coestablishment of persistent infection and oncogenic transformation of hamster embryo cells by equine herpesvirus type 1 preparations enriched for defective interfering particles. - Robinson, R A (1980)
Infection of permissive hamster embryo cells with virus preparations enriched for defective interfering (DI) particles of equine herpesvirus type 1 (EHV-1) resulted in persistent infection and oncogenic transformation. Six cell lines, designated DI-5 to -10, exhibited biological properties (immortality, increased saturation density, growth in soft agar, etc.) inherent to transformed cells, but 2 to 18% of the total cells in these cell lines were shown to release virus as judged by electron microscope studies and infectious center assays. The released virus was shown to be standard EHV-1 and not to contain DI particles as determined by density measurements of the viral DNA in the analytical ultracentrifuge and by interference assays using the released virus. Tumorigenicity studies revealed that inoculation of these persistently infected cells into newborn LSH inbred hamsters resulted in a lethal, fulminating hepatitis, whereas inoculation into older immunocompetent hamsters (+4 weeks) led to the development of metastatic fibrous sarcomas. Tumor cell lines (DI-5T to -10T) established from these sarcomas were shown to be transplantable and virus nonproducers. Hybridization analyses of cellular DNAs from DI transformed and tumor cell lines using 32P-labeled genomic EHV-1 DNA as probes indicated that the whole virus genome was detectable in multiple copies (23 to 45) in the transformed cells and that DNA sequences representing only 43.5 to 56.6% of the virus genome were present in amounts of 2 to 4 copies per cell in the DI tumor cells. Expression of these viral DNA sequences as demonstrated by the detection of virus-neutralizing antibodies, 50% neutralizing dose titers ranging from 1:50 to 1:1,000, in the sera of animals inoculated with either the virus-producing transformed cells or the virus-nonproducing tumor cells. Further, EHV-1-specific proteins were detected in the membrane and the perinuclear region of bothDI transformed and tumor cells by indirect immunofluorescent assays using antisera against EHV-1 structural antigens, EHV-1 nonstructural antigens, or preparations of EHV-1 DI particles. The roles of DI particles in mediating persistent infection and cellular transformation are discussed.